THE DIALECTICS OF MYTH AND HISTORY: EXPLORING AND DECODING THE CIRCLE OF REASON BY AMITAV GHOSH. - Kumar, Sooraj; S., Seema Rajan (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The Circle of Reason by Amitav Ghosh is a celebration of the fictional arras of myth, history, and rationality. It inevitably offers a glowing and an intricate exploration of human life across assorted cultures and topographies. The novel dextrously blends the mythical narratives with historical reasoning and sturdily challenges the conventional restrictions between fact and fiction. Ghosh’s portrayal of the protagonist, Alu, becomes a vehicle to examine the intersections of tradition and modernity, myth and logic, as well as the cultural conflicts that arise rapidly in a globalizing world. The novel, through its non-linear narrative, draws upon allegorical elements from Indian mythology while simultaneously engaging with historical events and scientific ideologies, such as the Enlightenment and colonial enterprise. It thus encompasses the finest tenets of New-Historicism in its journey of human exploration.